2019
DOI: 10.1108/ijopm-01-2018-0010
|View full text |Cite
|
Sign up to set email alerts
|

The relative importance of improvement routines for implementing lean practices

Abstract: Purpose-This paper examines whether and when improvement routines are critical for implementing lean practices in small-and medium-sized manufacturing enterprises (SMEs). Improvement routines such as "employees initiate and carry through improvement activities" are generally seen as an important means to achieve the full benefit of structural lean interventions. Womack and Jones (2003) suggest that these improvement routines should be developed as the company becomes more experienced in lean. The purpose of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 54 publications
0
31
0
Order By: Relevance
“…While lean manufacturing is a widely recognized management innovation and has been implemented in multiple fields (Lyonnet and Toscano 2014;Vlachos 2015;Knol et al 2018), the difficulties and failures of its implementation have also been highlighted (Ansari, Reinecke, and Spaan 2014;Boyer and Sovilla 2003;Dubouloz 2013;Jedynak 2015; Mart ınez-Jurado and Moyano-Fuentes 2014). Current criticisms associated with lean manufacturing, as a management innovation, mainly deal with the way it has been implemented rather than its fundamental principles (Mart ınez-Jurado and Moyano-Fuentes 2014; Ozelkan and Galambosi 2009).…”
Section: Introductionmentioning
confidence: 99%
“…While lean manufacturing is a widely recognized management innovation and has been implemented in multiple fields (Lyonnet and Toscano 2014;Vlachos 2015;Knol et al 2018), the difficulties and failures of its implementation have also been highlighted (Ansari, Reinecke, and Spaan 2014;Boyer and Sovilla 2003;Dubouloz 2013;Jedynak 2015; Mart ınez-Jurado and Moyano-Fuentes 2014). Current criticisms associated with lean manufacturing, as a management innovation, mainly deal with the way it has been implemented rather than its fundamental principles (Mart ınez-Jurado and Moyano-Fuentes 2014; Ozelkan and Galambosi 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The NCA method has been adopted in multiple scientific disciplines such as PSM (Van der Valk et al, 2016), educational sciences (Fredrich et al, 2018;Karwowski et al, 2017), psychology (Luther et al, 2017;Sorjonen & Melin, 2019), operations management (Knol et al, 2018(Knol et al, , 2019, hospitality management (W. Lee & Jeong, 2019), sociology and marketing (Leischnig et al, 2018). NCA has some similarities with Qualitative Comparative Analysis, which, however, tries to identify combinations of factors (Ragin, 1987) but does not test if individual conditions are necessary for effectiveness, i.e.…”
Section: Nca -A New Methods For Measuring Necessary Conditions For Performancementioning
confidence: 99%
“…About the lean operational processes (1.2, Table 4), evidences of a culture in favour of continuous improvement were confirmed. Organizational learning is the core of continuous improvement (Knol et al, 2019). It was observed that the teams receive diverse trainings about LM and tools; the operators have the autonomy to make routine decisions and to suggest operational improvements.…”
Section: Case 2 -Company Bmentioning
confidence: 99%